2016
DOI: 10.1017/s000748531600078x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of a Moroccan strain ofStreptomyces phaeochromogenesLD-37 on larvae, pupae and adults of the Mediterranean fruit fly,Ceratitis capitata(Diptera: Tephritidae)

Abstract: The Mediterranean fruit fly (medfly), Ceratitis capitata, is considered the most important fruit pest worldwide. Its management is mainly based on the use of chemical insecticides. Although these conventional pesticides are effective at high doses, they cause considerable human health and environment problems. Thus, the aim of this study was to assess insecticidal activity of Moroccan actinobacteria against C. capitata. A total of 12 preselected actinobacteria isolated from various Moroccan habitats were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 69 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Although the antifeedant, larvicidal, and growth inhibitory activity of the secondary metabolites isolated from Streptomyces spp. has been reported [ 4 , 7 , 54 , 55 ], the inhibition of oviposition has not been adequately studied yet. Taking into account high-level insecticidal, larvicidal, and spawn suppressing the activities of the strain KR0006, interest has arisen in conducting additional experiments of increasing the activity of this strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the antifeedant, larvicidal, and growth inhibitory activity of the secondary metabolites isolated from Streptomyces spp. has been reported [ 4 , 7 , 54 , 55 ], the inhibition of oviposition has not been adequately studied yet. Taking into account high-level insecticidal, larvicidal, and spawn suppressing the activities of the strain KR0006, interest has arisen in conducting additional experiments of increasing the activity of this strain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the antimycin family of compounds has exhibited a broad spectrum of insecticidal and antifungal activities. [4,7,54,55], the inhibition of oviposition has not been adequately studied yet. Taking into account high-level insecticidal, larvicidal, and spawn suppressing the activities of the strain KR0006, interest has arisen in conducting additional experiments of increasing the activity of this strain.…”
Section: Plos Onementioning
confidence: 99%
“…The 210 Actinobacteria isolates used in this study were from the collection of the Laboratory of Biology and Biotechnology of Microorganisms, Cadi Ayyad University, Marrakesh, Morocco. They were isolated from various Moroccan habitats including rhizospheric soils and endophytes of endemic aromatic and medicinal plants [ 13 , 14 ]. All strains were maintained in glycerol (20%) at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These methods could be utilized as control measures to meet the new international market requirements regarding fruit protection, quality, healthy environment, and human health. 28,29 Consequently, sustainable approaches to chemical control like biopesticides, 30,31 the sterile insect technique (SIT), 19 cold treatment 32 and mass trapping 33 are used. Other methods, such as the continued release of self-limiting medfly strains, are also being studied.…”
Section: Control Approaches In Moroccomentioning
confidence: 99%